Srijaya Industries Sdn. Bhd. / Nur Asma’at Amira Ismail - Ismail, Nur Asma’at Amira (2022)
Sirijaya Industries Sdn Bhd is a Malaysian firm that specialises in the production of plastic lamp holders and starters for fluorescent light fixtures. The emphasis of this company review is on the LED light provided by Sirijaya Industries, which will be investigated, defined, and analysed, as well as their current problems and solutions. The first problem regarding their product is a premature system failure. Most LED driver circuits use electrolytic capacitors to absorb voltage surges that may be present on the AC line. As for the next problem is their product overheating. Many obvious design factors, such as insufficient heat sinking and excessive LED strength, can cause LED overheating. The third problem is low color rendering index of the products. It effect of an illuminant on the color appearance of objects by conscious or subconscious comparison with their color appearance under a reference illuminant. Aside from that, there a few solutions to that problems primarily are do innovation, Research & Development with a new alternative such as using non-woven fabric material. This is due to the non-woven fabric that are eco-friendly, biodegradable, lightweight and convenient to use as plant nursery bag. The next solutions are existing cooling mode of the lighting system. There are several ways to cool LED lighting devices now, and they can be split into two categories: package-level cooling and lighting-level cooling. Finally, using phosphor transfer, transform the coloured light to white light. PC-WLEDs (phosphorus-converted white light-emitting diodes) are highly energy-efficient light sources for artificial lighting. Sirijaya Industries can also employ more quality control personnel to ensure that only decent products with no defects are marketed to consumers. All of these solutions are thought to help Sirijaya Industries in producing high-quality products for their customers, allowing them to continue to expand, develop, and achieve more in the future.